Altmetrics indicators in Brazilian Journals of Information Science - Ernesto Manhique, Ilidio Lobato; Rodrigues, Fernando de Assis [UNESP]; Goncalves Sant'Ana, Ricardo Cesar [UNESP]; Silva Casarin, Helen de Castro [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2019)
The growing informational volume boosted by the development of Information and Communication Technologies has increased the focus on the seek for visibility of publications in the scientific field, raising the degree of relevance of the academic recognition by researchers, resulting in questions about the perception of the traditional measures of evaluation of the academic impact. The goal of this study is to identify the visibility of the Brazilian scientific production of Information Science area, from the periodicals indexed in BRAPCI (Referral Database of Journals Papers in Information Science), with the use of data of altmetric indicators from Online Social Networking services and databases related with reference management websites. The results show that the altmetric data still have a low level of adherence in the Brazilian journals context related to Information Science. Among the factors involved, stand out the lack of identifiers in approximately eighty percent of the journals indexed by BRAPCI and the low level of mentions on publications into the Online Social Networks services. It is concluded that these alternative metrics to complement the traditional metrics still need to be more explored theoretically and, as a requirement, technically through an implement process by publishers.
Keywords: Altmetrics; Social Networks; Information Science; Database of references from Information Science Journals; Brazil